Spinal Cord Stimulator Explantation: Motives for Removal of Surgically Placed Paddle Systems. Issue 4 (20th November 2017) - Dupré, Derrick A.; Tomycz, Nestor; Whiting, Donald; Oh, Michael
Abstract: Background: Despite requiring successful trials prior to implantation, spinal cord stimulation (SCS) systems for pain are often later removed. Removing surgically implanted hardware subjects patients to the risks and discomfort of a second surgery, threatens the cost‐effectiveness of SCS, and limits the perceived durability of SCS technology for pain problems. Objective: To investigate patterns of reasons given among patients who underwent SCS explant surgery (SCSES). Methods: Retrospective review of SCSES cases over 17 years at Allegheny General Hospital, Pittsburgh, PA. Results: 165 patients underwent SCSES between 1997 and 2014. The top 3 reasons for explantation were inadequate pain control (IPC; 73%), hardware discomfort (22%), and need for magnetic resonance imaging (MRI) (10%). Other less frequent reasons were infection (9%), painful dysesthesias (9%), electrical arcing (4%), resolution of inciting symptoms (4%), weakness (2%), pseudomeningocele (1%) and muscle spasms (1%). Conclusion: Inadequate pain control is the most common reason for SCSES. Advances in technology are needed to improve the quality and duration of pain control, as well as to design improvements to make the hardware more comfortable. A significant number of implants are removed due to need for MRI, a fact obviating the need for MRI‐compatible systems. Patients considering SCS paddle lead placement should be counseled on the most common reasons for later explantation.